PENGARUH JUMLAH PINJAMAN DAN TINGKAT BUNGA PINJAMAN TERHADAP PENDAPATAN LPD DI LPD DESA ADAT BONGKASA - I Kadek Diarta; Made Yudi Darmita; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2021)
This study aims to examine the effect of loan amount and loan interest rate on LPD income in Bongkasa traditional village. The dependent variable in this study is income (Y), while the independent variable in thisstudy is the amount of loans (X1), the interest rate on loans (X2). The population of this study were customers of the Bongkasa traditional village LPD. The sample in this study was selected by purposive sampling method and obtained a sample of 119 LPD customers in Bongkasa Traditional Village. The research method used is quantitative research with data analysis using multiple regression analysis processed with the SPSS 22 statistical program. The results of the analysis show the regression model Y = a + b1 X1 + b2 X 2 Y = 6.500 + 0.258X1 + 0.801X2. The conclusions obtained are partially. When viewed from the variable coefficient of Loan Amount (X1), Loan Interest Rate (X2). has a positive and significant influence on LPD Income in the Bongkasa Adat village with a significance value of the amount of loans of 0.258, and the Loan Interest Rate of 0.801 has a significant positive effect on LPD Income in the Bongkasa Adat village. The amount of influence of the amount of loans, and the loan interest rate on LPD income in the Bongkasa traditional village is 70.3% and the remaining 29.7% is influenced by other variables not examined in this study.